The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1759759
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and economic burden of psychogenic non-epileptic seizures in patients applying for disability benefits due to epilepsy

Abstract: Background Psychogenic non-epileptic seizures (PNES) resemble epileptic seizures and are often misdiagnosed as epilepsy. Objective To investigate the frequency of PNES and to calculate the economic burden of the patients who admitted to video-electroencephalographicmonitoring (VEM) to obtain a diagnosis of epilepsy in order to apply for disability retirement. Methods The present retrospective study included 134 patients who required disability reports between 2013 and 2019 and had their def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Pekos and coworkers concluded that early diagnosis and psychosocial support are key to reduce the financial burden on the health system, as well as, to increase the quality of life of PNES patients, after analyzing charts on 134 patients who applied to receive disability reports. 8 This is certainly a wishful goal and, at the same time, a rather challenging one. An editorial at Neurology discussed the delay between the onset of seizures and the correct diagnosis of PNES, estimating an average of 7 years, along with other shocking figures.…”
mentioning
confidence: 99%
“…Pekos and coworkers concluded that early diagnosis and psychosocial support are key to reduce the financial burden on the health system, as well as, to increase the quality of life of PNES patients, after analyzing charts on 134 patients who applied to receive disability reports. 8 This is certainly a wishful goal and, at the same time, a rather challenging one. An editorial at Neurology discussed the delay between the onset of seizures and the correct diagnosis of PNES, estimating an average of 7 years, along with other shocking figures.…”
mentioning
confidence: 99%